Halogen bonding interlocked rotaxanes and transition metal-based host systems for charged guest recognition and sensing - Munasinghe, AVK (2022)
The main theme of this thesis is to incorporate multiple convergent halogen bonding (XB) donor motifs into anion binding sites of mechanically interlocked rotaxanes and transition metal-based host architectures and investigate their anion and ion-pair recognition capabilities.